Tunnel-structured Na0.54Mn0.50Ti0.51O2 and Na0.54Mn0.50Ti0.51O2/C nanorods as advanced cathode materials for sodium-ion batteries1. Issue 40 (18th May 2015) - Jiang, Xiaolei; Liu, Shuo; Xu, Huayun; Chen, Liang; Yang, Jian; Qian, Yitai
<x xml:space="preserve">Abstract</x> Tunnel-structured Na0.54Mn0.50Ti0.51O2 nanorods have been synthesized by a facile molten salt method.